2001
DOI: 10.1103/physrevlett.86.5148
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Flux Line Lattice Transition into Square Symmetry in SuperconductingLuNi2B2C

Abstract: We have investigated the temperature dependence of the H c flux line lattice structural phase transition from square to hexagonal symmetry, in the tetragonal superconductor LuNi2B2C (Tc = 16.6 K). At temperatures below 10 K the transition onset field, H2(T ), is only weakly temperature dependent. Above 10 K, H2(T ) rises sharply, bending away from the upper critical field. This contradicts theoretical predictions of H2(T ) merging with the upper critical field, and suggests that just below the Hc2(T )-curve th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…12,13 In combination with non-negligible fluctuation effects, the competition leads to unique vortex dynamics right below the H c2 line in the borocarbides, namely a reentrant vortex lattice transition. 9 Fluctuation effects near the upper critical field line wash out the anisotropy effect, stabilizing the Abrikosov hexagonal lattice. 14, 15 Here, we report the first observation of paramagnetic effects in the dc magnetization M of the mixed state of LuNi 2 B 2 C. The kink-like feature in M and the corresponding specific heat feature for H ≥ 30 kOe signify the reentrant FLL transition, which is consistent with the low-field FLL transition line inferred from small angle neutron scattering (SANS).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…12,13 In combination with non-negligible fluctuation effects, the competition leads to unique vortex dynamics right below the H c2 line in the borocarbides, namely a reentrant vortex lattice transition. 9 Fluctuation effects near the upper critical field line wash out the anisotropy effect, stabilizing the Abrikosov hexagonal lattice. 14, 15 Here, we report the first observation of paramagnetic effects in the dc magnetization M of the mixed state of LuNi 2 B 2 C. The kink-like feature in M and the corresponding specific heat feature for H ≥ 30 kOe signify the reentrant FLL transition, which is consistent with the low-field FLL transition line inferred from small angle neutron scattering (SANS).…”
mentioning
confidence: 99%
“…6,7,8,9 The transition from square to hexagonal vortex lattice occurs due to the competition between sources of anisotropy and vortex-vortex interactions. The repulsive nature of the vortex interaction favors the hexagonal Abrikosov lattice, whose vortex spacing is larger than that of a square lattice.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…First, Gammel et al 36 showed that H 2 increases as ℓ is reduced by increasing x. Later on, Eskildsen et al 38 showed that H 2 (T ) also rises as T increases.…”
Section: Results and Discusionsmentioning
confidence: 99%